MDR-1 C3435T polymorphism may affect blood pressure in resistant hypertensive patients independently of its effects on aldosterone release. (June 2014) - Lacchini, Riccardo; Figueiredo, Valéria N; Demacq, Caroline; Coeli-Lacchini, Fernanda B; Martins, Luís C; Yugar-Toledo, Juan; Coca, Antonio; Tanus-Santos, Jose E; Moreno, Heitor
Aldosterone increases plasma volume and may be involved with resistant hypertension. P-glycoprotein is a transporter involved in the distribution and disposition of aldosterone, and is encoded by the MDR-1 gene. MDR-1 has functional polymorphisms that may affect P-glycoprotein expression. We hypothesized that the C 3435 T polymorphism in MDR-1 could be associated with resistant hypertension and with changes in hypertension-related parameters. We studied 105 healthy volunteers, 137 hypertensive patients responsive to treatment, and 83 resistant hypertensive patients. While we found no association of C 3435 T genotypes with resistance to treatment ( p = 0.31), C allele was associated with hypertension ( p = 0.03). Furthermore, the CC genotype was associated with higher systolic blood pressure ( p < 0.01 for both daytime and nighttime, respectively) and diastolic blood pressure ( p < 0.01 for both daytime and nighttime, respectively). This effect was probably independent of aldosterone, as we found no differences in aldosterone plasma levels, nor in pulse wave velocity (PVW) between the genotypes groups ( p = 0.77 and p = 0.48, respectively). Our results show an association of C 3435 T with hypertension and with blood pressure levels in resistant hypertensive subjects.